2001
DOI: 10.1068/p3092
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Suppression of Tilt Sensations during Linear Horizontal Self-Motion in the Dark

Abstract: On the basis of models of otolith functioning, one would expect that, during sinusoidal linear self-motion in darkness, percepts of body tilt are experienced. However, this is normally not the case, which suggests that the otoliths are not responsive to small deviations from the vertical of the gravito-inertial force vector acting on them. Here we show that this is incorrect. Subjects usually know on what kind of linear motion device they are (going to be) moved, having seen it prior to experimentation. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 16 publications
4
43
0
Order By: Relevance
“…Therefore, it is clear that the pattern of multisensory stimulation does not always have to be consistent to induce compelling vection and generate substantial vection improvements. However, it should also be noted that, in addition to the contribution of retinal and extra-retinal information, higher-level cognitive (see Palmisano and Chan 2004;Wertheim et al 2001) and contextual factors (see Wright et al 2006) have also been suggested to play a role in the suppression and/or enhancement of illusory self-motion. Therefore, future research should further examine the contribution of the different sensory systems as well as the relative importance of cognitive and contextual information to the perception of selfmotion and vection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is clear that the pattern of multisensory stimulation does not always have to be consistent to induce compelling vection and generate substantial vection improvements. However, it should also be noted that, in addition to the contribution of retinal and extra-retinal information, higher-level cognitive (see Palmisano and Chan 2004;Wertheim et al 2001) and contextual factors (see Wright et al 2006) have also been suggested to play a role in the suppression and/or enhancement of illusory self-motion. Therefore, future research should further examine the contribution of the different sensory systems as well as the relative importance of cognitive and contextual information to the perception of selfmotion and vection.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, since in the absence of vision, perception of vertical is altered by the changing gravito-inertial vector that results from any acceleration not aligned with the constant gravitational background force (i.e., the hilltop illusion) [14], [18], [19], [47]. In this study, no visual tilt is present in the visual input other than the visual tilt directly resulting from self-generated head tilts.…”
Section: Discussionmentioning
confidence: 93%
“…This may be attributed to the assumption that not only idiothetic information is taken into account by the CNS, i.e., information gained by inertial sensors or information such as efference copies, but also certain pre-existing knowledge or cognitive information [22,23,25]. Especially these latter cues are likely to vary between subjects, and become more important the less idiothetic information is available.…”
Section: Discussionmentioning
confidence: 99%